Assessment of Groundwater Depletion and quality in western Indian river basins using GIS and Remote Sensing Techniques (Journal of Advances and Scholarly Researches in Allied Education, 2023)
To settle water shortage and safeguard water quality, surveying groundwater assets is of most extreme significance, especially in regions encountering developing anthropogenic tensions and ecological changes. In this review, geographic data frameworks (GIS) and remote sensing techniques are joined to examinations groundwater quality and exhaustion in the Western Indian River Basins. There is a developing requirement for groundwater assets in the Western Indian River Basins because of impressive changes in land use, populace increment, and horticultural practices. The production of proficient observing and the executive’s frameworks has become essential because of these changes. In this present circumstance, GIS gives areas of strength for a for the review and perception of spatial information, while Remote Sensing gives significant data about changes in land cover and hydrological processes. In view of the coordinated utilization of remote sensing and Geological Data Frameworks (GIS), groundwater research has been finished in the Western Doon valley to characterize the groundwater potential and groundwater quality zones suitable for private purposes. The Western Doon Valley is loaded up with post-Siwalik fluvial and flotsam and jetsam stream stores from the late Quaternary-Holocene and possesses immense synclinal box in the creating fold-push arrangement of the sub-Himalaya.